Analisis Pengaruh desain Produk dan Kualitas Produk terhadap Keputusan Pembelian Motor Honda Beat di Kabupaten Karawang - Firmansah, Syarif; Isyanto, Puji; Sumarni, Neni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of product design and product quality on purchasing decisions for Honda Beat motorcycles in Karawang Regency. Using a quantitative research design, this study involved 100 respondents from prospective consumers of Honda Beat motorcycles. Data were collected through questionnaires and analyzed using SPSS 26 software. The results showed that product design had a positive and significant influence on purchasing decisions, with a regression coefficient value of 0.322. Product quality was also shown to have a positive and significant influence on purchasing decisions, with a regression coefficient value of 0.348. Multiple linear regression tests revealed that product design and product quality simultaneously influenced purchasing decisions, with a determination coefficient value (R²) of 71.9%, indicating that 71.9% of the variation in purchasing decisions could be explained by these two variables. This study contributes to the understanding of how motorcycle product design and quality can influence consumer purchasing decisions in the Indonesian automotive market. These findings are expected to provide guidance for motorcycle manufacturers, especially Astra Honda Motor, in designing better products to meet consumer expectations and win the competition in the market.